Placental trophoblast syncytialization potentiates macropinocytosis via mTOR signaling to adapt to reduced amino acid supply - Shao, Xuan; Cao, Guangming; Chen, Dunjin; Liu, Juan; Yu, Bolan; Liu, Ming; Li, Yu-Xia; Cao, Bin; Sadovsky, Yoel; Wang, Yan-Ling (Proceedings of the National Academy of Sciences - PNAS, 2021)
During pregnancy, the appropriate allocation of nutrients between the mother and the fetus is dominated by maternal–fetal interactions, which is primarily governed by the placenta. The syncytiotrophoblast (STB) lining at the outer surface of the placental villi is directly bathed in maternal blood and controls feto–maternal exchange. The STB is the largest multinucleated cell type in the human body, and is formed through syncytialization of the mononucleated cytotrophoblast. However, the physiological advantage of forming such an extensively multinucleated cellular structure remains poorly understood. Here, we discover that the STB uniquely adapts to nutrient stress by inducing the macropinocytosis machinery through repression of mammalian target of rapamycin (mTOR) signaling. In primary human trophoblasts and in trophoblast cell lines, differentiation toward a syncytium triggers macropinocytosis, which is greatly enhanced during amino acid shortage, induced by inhibiting mTOR signaling. Moreover, inhibiting mTOR in pregnant mice markedly stimulates macropinocytosis in the syncytium. Blocking macropinocytosis worsens the phenotypes of fetal growth restriction caused by mTOR-inhibition. Consistently, placentas derived from fetal growth restriction patients display: 1) Repressed mTOR signaling, 2) increased syncytialization, and 3) enhanced macropinocytosis. Together, our findings suggest that the unique ability of STB to undergo macropinocytosis serves as an essential adaptation to the cellular nutrient status, and support fetal survival and growth under nutrient deprivation.